PEMBELAJARAN MENULIS TEKS EKSPLANASI PADA SISWA SMP KELAS VIII MENGGUNAKAN MODEL PICTURE AND PICTURE BERBANTUAN MEDIA POWER POINT - Chintia Ifanka (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
This study aims to examine the implementation in learning to write explanatory texts using picture and picture models assisted by power point media. examine teacher and student responses to learning to write explanatory texts by using picture and picture models assisted by power point media and examine students' difficulties when completing explanatory text writing questions. The research method used is descriptive qualitative. Subjects in the study were students of class VIII Mutiara 4 Bandung Junior High School totaling 42 students and were given treatment in the form of models and learning media for three meetings. The instruments in this study were observation sheets, questionnaires, and test sheets. The results of the observation sheet if accumulated from three meetings for teacher activities scored 79.33% with a high category and three meetings for student activities scored 78% with a high category. On the questionnaire sheet the teacher's response was very good, guessed by the percentage obtained after being analyzed on the questionnaire the teacher got a percentage of 87.5% while for student responses the average percentage of results was 85.1% with very high descriptive analysis criteria. Difficulties experienced by students when working on problems as many as 8 students whose grades below the KKM with an overall average obtained 73.52. From the above data it can be concluded that learning to write explanatory texts using picture and picture models assisted by power point media is very effectively applied in learning